Effect of latent heating on mesoscale vortex development during extreme precipitation: Colorado, September 2013 - Morales, Annareli, author; Kreidenweis, Sonia M., advisor; Schumacher, Russ S., advisor; Ramirez, Jorge A., committee member (Colorado State University. Libraries, 2014)
From 9-16 September 2013, a slow-moving cut-off low in the southwestern U.S. funneled unseasonal amounts of moisture to the Colorado Front Range, resulting in extreme precipitation and flooding. The heaviest precipitation during the September 2013 event occurred over the northern Colorado Front Range, producing a 7-day total of over 380 mm of rain. The flash flooding caused over $3 billion in damage to property and infrastructure and resulted in eight fatalities. This study will focus on the precipitation and mesoscale features during 11-12 September 2013 in Boulder, CO. During the evening of 11 September, Boulder experienced flash flooding as a result of high rain rates accumulating over 180 mm of rain in 6 hours. From 0400-0700 UTC 12 September, a mesoscale vortex (mesovortex) was observed to travel northwestward towards Boulder. This circulation enhanced upslope flow and was associated with localized deep convection. The mesovortex originated in an area common for the development of a lee vortex known as the Denver Cyclone. We hypothesize that this mesoscale vortex is not associated with lee vortex formation, such as the Denver Cyclone, but developed through the release of latent heat from microphysical process. The Advanced Research Weather Research and Forecast (ARW) model was used to 1) produce a control simulation that properly represented the evolution and processes of interest during the event and 2) test the importance of latent heating to the development and evolution of the mesovortex. The results from various latent heating experiments suggested that the mesovortex did not develop through lee vortex formation and the latent heat released just before and during the mesovortex event was important to its development. Results also showed latent heating affected the flow field, resulting in a positive feedback between the circulation, associated low-level jet, and convection leading to further upslope flow and precipitation development. Further experiments showed condensation of cloud water was the dominant microphysical process responsible for a positive vertical gradient in latent heating near the surface. This gradient led to potential vorticity generation; a similar mechanism to that of a mesoscale convective vortex, except closer to the surface. Finally, an experiment where the latent heating was reduced by half after 1800 UTC 11 September resulted in no mesovortex development and a substantial decrease in precipitation. The results from this study have relevant implications to the representation of microphysical processes in numerical weather prediction models. The capability to forecast the development of these mesovortices and their subsequent environmental and hydrological effects could be critical for decision makers and the public, given their association with high rain fall rates.
Keywords: potential vorticity; Colorado Flood; extreme precipitation; latent heating; mesoscale vortex